Blood pressure variability and urine flow in the conscious dog - Nafz, Benno; Ehmke, Heimo; Wagner, Claus D.; Kirchheim, Hartmut; Persson, Pontus B. (American journal of physiology. Renal physiology, 1998)
Pressure-dependent urine production is considered to be a major factor in long-term blood pressure control. The phenomenon has been well characterized for fixed levels of renal perfusion pressure (RPP), but the influence of physiological fluctuations in RPP and spontaneous variations in renal blood flow (RBF) on short-term urine flow (UV) remain unclear. To clarify this issue, we studied the interdependence of RPP, RBF, and UV in 13 conscious foxhounds during a single-step pressure reduction, under normal conditions, and with induced pressure changes. Reducing RPP in a single step to ∼80 mmHg revealed short response times of RBF (0.4 ± 0.1 s, n = 7) as well as of UV (8.1 ± 0.8 s, n = 7). Under control conditions, UV was coupled with spontaneous variations of RBF (r = 0.94,P < 0.001), in contrast to RPP, which showed no significant correlation with UV (r = 0.09,P = NS). To discern the pressure and blood flow dependency of UV at a reduced RPP, we induced 0.9-mHz blood pressure oscillations (80 ± 10 mmHg), which phase shifted RPP and RBF. Conversely, under these conditions, UV was dependent on RPP (r = 0.95,P < 0.001). These results suggest that spontaneous fluctuations in RBF around a normal baseline level lead to concomitant changes in urine production, in contrast to physiological short-term oscillations in RPP, which are not correlated to changes in UV. However, during induced oscillations of perfusion pressure, the blood flow dependence was no longer observed and UV was entirely pressure dependent.